Large-Scale Implementation of Bioenergy With Carbon Capture and Storage in the Swedish Pulp and Paper Industry Involving Biomass Supply at the Regional Level - Karlsson, Sebastian; Eriksson, Anders; Normann, Fredrik; Johnsson, Filip (Frontiers in Energy Research, 2021)
Bioenergy with carbon capture and storage (BECCS) has been identified as a possible major contributor to efforts to reach ambitious climate targets through the provision of negative emissions–offsetting residual fossil emissions in “hard-to-abate” sectors and accomplishing net-negative emissions. The pulp and paper industry is the single largest consumer of biomass in Sweden, with many large point sources of biogenic CO2 emissions that could be captured. This work investigates the biomass supply required for large-scale implementation of BECCS in the pulp and paper industry. Logging residues are considered as a fuel to supply the additional energy demand imposed by the capture plant, and the potential of these residues is evaluated in a case study that includes four pulp and paper mills located in regions of Sweden with different conditions for biomass supply. Two of the mills are located in southern Sweden, where there is strong competition for logging residues from the heating sector, and two of the mills are located in northern Sweden, where the competition is weaker. We show that implementing carbon capture at the four pulp and paper mills using regional logging residues to supply the additional heat demand required by the capture process (the reboiler heat demand) has the potential to capture around 4.6 Mt CO2/year. The results also show that the fuel share of the capture cost, i.e., the cost to supply the reboiler heat demand with regional logging residues, is 22–30 €/tCO2 captured, where the lower value corresponds to regions with weaker competition for logging residues (in this study, northern Sweden). In regions that have competition for logging residues, the possibility to increase the regional supply of logging residues to fuel the capture process while maintaining mill production output is limited, which in turn limits the possibilities to generate negative emissions via BECCS. In contrast, in regions with a low level of competition and strong availability of logging residues, there is an additional potential for logging residues to cover the additional heat demand required for CCS implementation.